Development of Duloxetine Hydrochloride Tablets for Delayed and Complete Release Using Eudragit L 100 - M. Yasmin Begum; Ali Alqahtani; Mohammed Ghazwani; Noura Abdullah Alhamood; Umme Hani; Avanthi Jajala; Mohamed Rahamathulla (International Journal of Polymer Science)
The purpose of the research was to optimize the preparation of duloxetine hydrochloride (duloxetine HCl) delayed release tablets. Duloxetine HCl produces a toxic substance called alpha-naphthol when duloxetine HCl is in contact with gastric fluid. Thus, duloxetine HCl when given orally needed a protective enteric coating that disable the delivery of duloxetine HCl in gastric fluid while enabling the drug delivery only in small intestine. Four different core tablets were prepared by direct compression technique, and the one which displayed quick disintegration and dissolution was chosen for enteric coating. The compressed tablets were enteric coated by dip coating technique. Since subcoating is required to safeguard the enteric coating, the core tablets were subcoated by using polymer HPMC K15M and then enteric coated with Eudragit L 100. The prepared tablets were assessed for the entire precompression and postcompression characteristics. FTIR study revealed the existence of all prominent peaks signifying its compatibility and authenticity. The in vitro studies showed that enteric-coated tablets were capable of restricting release in acidic media. The formulation F8 was optimised with 5% and 15% increase in weight of seal coat and enteric coat with good dissolution profile. Stability studies revealed that the optimized formulation was intact without any deterioration for 3 months. In conclusion, the optimized formulation could resist the drug release in acidic environment of gastrointestinal region and release the drug at a time once the tablet reaches the intestine.